2012
DOI: 10.1016/j.rser.2012.02.058
|View full text |Cite
|
Sign up to set email alerts
|

Wind energy in Egypt: Economic feasibility for Cairo

Abstract: Motivated by the rise of the electricity tariffs applied on industrial customer and the frequent electricity cut offs recently experienced in Egypt, this paper assesses the economic feasibility of installing a stand alone wind energy technology by an industrial customer who seeks to reduce his dependency on the national grid. For this purpose, the wind energy potential at the wind regime of Cairo was chosen to be assessed using half an hour wind speed data for a full one-year period (2009). The Weibull paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…The analysis revealed that the majority of the authors usually apply two or three methods to assess the projects. The methods include net present value (NPV), internal rate of return (IRR) and the payback period (Lima and Filho, 2010, Recalde, 2010, Parissis et al, 2011, Hamouda, 2012, O'Connor et al, 2013.…”
Section: Investment Project Assessment Methods Applied Both In Theorementioning
confidence: 99%
See 1 more Smart Citation
“…The analysis revealed that the majority of the authors usually apply two or three methods to assess the projects. The methods include net present value (NPV), internal rate of return (IRR) and the payback period (Lima and Filho, 2010, Recalde, 2010, Parissis et al, 2011, Hamouda, 2012, O'Connor et al, 2013.…”
Section: Investment Project Assessment Methods Applied Both In Theorementioning
confidence: 99%
“…The last important factor is the economic lifetime of onshore turbines which is considered to be 20 years in many studies (Yue, 2009;Lima, 2010;Parissis, 2011;Hamouda, 2012).…”
Section: Rasa Kanapickienė Arvydas Kanapickas 235mentioning
confidence: 99%
“…Air density depends essentially on pressure and temperature, and air density can be calculated using the ideal gas law [20]. Air density is given as:…”
Section: Wind Speed Datamentioning
confidence: 99%
“…The average output power of a wind turbine ( ave P ) can be estimated as Eq. (2) where the probability density function ( ) f v represents the fraction of duration of wind speed v. The most commonly used model to express the wind speed probability distribution f(v) is the Weibull distribution [14][15][16]. p v is wind turbine output power curve [9].…”
Section: Wind Turbine Capacity Factor and Output Energymentioning
confidence: 99%